The impact of aminoglycoside exposure on soil and plant root-associated microbiota: a meta-analysis - Jessica L. Coates; Ashanti J. Lawson; Kathleen Bostick; Mentewab Ayalew (Environmental Evidence)
Abstract Background Exposure to aminoglycosides, a class of potent bactericidal antibiotics naturally produced by soil microorganisms and commonly used in agriculture, has the potential to cause shifts in the population dynamics of microorganisms that impact plant and soil health. In particular, aminoglycoside exposure could result in alterations of the soil and plant root-associated bacterial species diversity and richness due to their potent inhibitory action on microbial growth, the creation of selective conditions for the proliferation of antibiotic-resistant bacteria, or a reduction in the ability to suppress soil pathogens. Previous studies have attempted to understand the relationship between aminoglycoside exposure and the plant-associated microbiota with varying results. Thus, this systematic review aims to survey all relevant published data to answer the question, “What is the impact of aminoglycoside exposure on the soil and plant root-associated microbiota?” Methods We searched 5 academic databases and 1 specialist organization database for scientific journal publications written in any language. Articles were included based on the criteria described in Coates et al., 2022. Included studies were subject to critical appraisal using the CEE Critical Appraisal Tool Version 0.2 (Prototype) to evaluate their susceptibility to confounding factors, misclassification bias, selection bias, attrition bias, reporting bias and analysis bias. Studies deemed to be high risk based on critical appraisal results were excluded from further analysis. Descriptive data analysis was performed for studies considered low or unclear for risk of bias. Meta-analyses were conducted for antibiotic resistance and microbial diversity. Review findings Out of 8370 screened records, 50 articles fulfilled the search criteria, and from these, 13 studies were included in meta-analysis. Most studies investigated the impact of aminoglycoside exposure on soil microbiota (93%) in a laboratory setting (62%), primarily from the United States (32%), China (24%), France, Switzerland and Germany (8%). A limited number of studies investigated the impact of aminoglycoside exposure on disease suppression, so it was excluded from meta-analysis. Therefore, our synthesis primarily details the impact of aminoglycoside exposure on the microbial diversity and antibiotic resistance of the soil microbiota. Overall, exposure to aminoglycosides did not result in a significant change in the microbial diversity. However, soil use, pH, and type of aminoglycoside used could be potential modifiers. Additionally, we observed an average 7% of the microbial population exhibiting resistance to aminoglycosides, with the relationship between the exposure concentration and the selection concentration emerging as a potential modifier. Conclusions Current research is limited by gaps in understanding the relationship between aminoglycoside exposure, microbial community dynamics, and disease suppression, as well as by insufficient data on less-studied aminoglycosides and key confounding factors. Current research also suggests a potential relationship between antibiotic concentrations used for exposure and selection of resistant bacteria. These findings emphasize the need for informed antibiotic management policies and rigorous, targeted research to better understand the relationship between soil factors and antibiotic concentrations used on the impact of aminoglycosides on soil microbiota.